TO STUDY THE OPERATION OF THE FRACTIONATING APPARATUS IN INCREASING THE EFFICIENCY OF SEPARATION OF HYDROCARBON FRACTIONS (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2024)
The rectification process is carried out in column apparatuses, and the apparatus has appropriate internal devices. With the help of these devices, gas mixture flow interconnections and necessary temperatures are provided. The internal devices of the column consist of plates with different structural designs or nozzles made of different materials, which provide gas-liquid interaction.